Implementation of Merdeka Belajar Differentiated Instruction in Science Learning to Improve Student’s Science Literacy - Saniatul Hidayah; Yudha Irhasyuarna; Maya Istyadji; Fahmi Fahmi (Postgraduate, University of Mataram, 2023)
The diversity of learning needs of students needs to be accommodated in learning. In addition, Indonesia's scientific literacy ability is still relatively low due to low interest or motivation to learn. Therefore, this study aims to describe the improvement of students' scientific literacy skills through independent differentiated instruction. This study used a pre-experimental type experimental methodÂ with a one-group pretest posttest design. The research sample was conducted by non-probability sampling using a type of purposive sampling. The subjects of this study were 33 students of class VII C SMP Negeri 7 Banjarmasin. Data collection techniques use test instruments, response questionnaires, and documentation. The data analysis technique uses t-test and N-gain test. The results showed that there was an increase in students' scientific literacy skills through the implementation of independent differentiated instruction which was shown by the results of the t sig test (0.000) < Î± = 0.05 with a large increase of 0.71 or 71.33% in the high category.